Structural basis for ubiquitylation by HOIL-1 - Wu, Qilong; Koliopoulos, Marios G.; Rittinger, Katrin; Stieglitz, Benjamin (Frontiers in Molecular Biosciences, 2023)
The linear ubiquitin chain assembly complex (LUBAC) synthesises linear Ub chains which constitute a binding and activation platform for components of the TNF signalling pathway. One of the components of LUBAC is the ubiquitin ligase HOIL-1 which has been shown to generate oxyester linkages on several proteins and on linear polysaccharides. Here we describe the crystal structure of a C-terminal tandem domain construct of HOIL-1 comprising the IBR and RING2 domains. The structure adopts an auto-inhibited conformation in which the catalytic cysteine of the RING2 domain is shielded by the adjacent IBR domain. Activation of HOIL-1 is triggered by linear tetra-Ub binding which enables HOIL-1 to mono-ubiquitylate linear Ub chains and polysaccharides. Interestingly, the structure reveals a unique bi-nuclear Zn-cluster which substitutes the second zinc finger of the canonical RING2 fold. We identify the C-terminal histidine of this bi-nuclear Zn-cluster as the catalytic base required for the ubiquitylation activity of HOIL-1. Our study suggests that the unique zinc-coordinating architecture of RING2 provides a binding platform for ubiquitylation targets.